BIG ENTERTAINMENT’S FILM AND MUSIC CREATION DESIGN: PLATFORM-BASED BUSINESS MODEL CANVAS AND ENTERPRISE ARCHITECTURE - Ruddin, Isra; Santoso, Handri; Indrajit, Richardus Eko; Dazki, Erick (Capture : Jurnal Seni Media Rekam, 2021)
BIG Entertainment is an application that offers unparalleled music and film entertainment. Previously, applications like Spotify were all about music, while Netflix, Joox, and Disney were all about movies. This entertainment combines movies and music into a single application. This research seeks to examine the Big Entertainment application's business model canvas. This study employs the literature review method, which gathers various scientific and relevant sources. The findings suggest that BIG Entertainment service providers work hard to expand their offerings in response to changing market trends and technology advancements. The business model offers both tangible and intangible assets for customers who require not only the final product (music service) but also a one-stop service. BIG Entertainment can generate profit while developing a distinctive and efficient business model if it successfully integrates tangible and intangible assets.